Effects of annealing temperature on the phase formation, optical, photoluminescence and magnetic properties of sol-gel YFeO3 films - Awang Kechik, Mohd Mustafa; Baqiah, Hussein; Al-Gaashani, Rashad; Al-Zahrani, Asla A.; Al-Hada, Naif Mohammed; Zhang, Na (Elsevier, 2022)
YFeO3 (YFO) thin films were deposited onto quartz substrates via sol-gel spin-coating technique and annealed at different temperature ranged between 650 and 900 °C. The impact of annealing temperature on the phase formation, microstructural, optical, photoluminescence (PL) and magnetic properties of the films were systematically investigated. X-ray diffraction analysis revealed an amorphous structure in film annealed at 650 °C and formation of hexagonal-YFO (h-YFO) phase in films annealed at 750–800 °C. The films annealed at 850–900 °C exhibited an orthorhombic-YFO (o-YFO) structure. Atomic force microscopy images of h-YFO films showed homogeneous surface with uniform particles size and shape. The particle size increased and had irregular shape in o-YFO films. The average particle size was 44 and 117 nm, while the root square roughness was 1.38 and 2.55 nm for h- and o-YFO films annealed at 750 and 850 °C, respectively. The optical band gap (Eg) was 2.53 and 2.86 eV for h- and o-YFO films annealed at 750 and 850 °C, respectively. The PL spectra of h-YFO films were red-shifted compared with that of o-YFO films. The PL emission related to near band edge was observed at 459.0 and 441.9 nm for h- and o-YFO films annealed at 750 and 850 °C, respectively. The magnetization was enhanced with the increasing of annealing temperature and has the value of 4.8 and 12.5 emu/cm3 at 5000 Oe for h- and o-YFO films annealed at 750 and 850 °C, respectively.